Impact of meningitis on intelligence and development: A systematic review and meta-analysis. - Deborah Christie; Harunor Rashid; Haitham El-Bashir; Faye Sweeney; Tim Shore; Robert Booy; Russell M Viner (PLoS ONE)
Background We undertook a systematic review and meta-analysis to address the question "what is the impact of meningitis on IQ and development." Methods Search: conducted using standardized search terms across Medline, PsychInfo and EMBASE to 06/2014. Eligibility: human studies of any infectious aetiology of meningitis reporting IQ or infant developmental age or stage outcomes. Quality: Centre for Evidence Based Medicine, Oxford, quality tools. Analysis: random effects meta-analysis by organism. Results 39 studies were included in the review, 34 providing data on IQ (2015 subjects) and 12 on developmental delay (382 subjects). Across all bacterial organisms, meningitis survivors had a mean IQ 5.50 (95% CI: -7.19, -3.80; I2 = 47%, p = 0.02) points lower than controls. IQ was significantly lower than controls for Neisseria meningitides (NM: 5 points) and Haemophilus influenzae b (Hib: 6 points) but not in viral meningitis, with only single studies included for Streptococcus pneumoniae (SP) and group B streptococcus (GBS). The pooled relative risk (RR) for low IQ (IQ<70) in survivors of bacterial meningitis compared with controls was 4.99 (95% CI: 3.17, 7.86) with no significant heterogeneity (I2 = 49%, p = 0.07). Developmental delay of approximately 0.5SD was reported in studies of bacterial meningitis but no delay in the only study of viral meningitis. Conclusions We found moderate evidence that surviving bacterial meningitis has a deleterious impact on IQ and development but no evidence that viral meningitis had meaningful cognitive impacts. Survivors of bacterial meningitis should be routinely offered screening for cognitive deficits and developmental delay in addition to hearing loss.